Stabilization of PE with Pomegranate Extract: Contradictions and Possible Mechanisms - Dóra Tátraaljai; Yun Tang; Emese Pregi; Erika Vági; Viola Horváth; Béla Pukánszky (MDPI AG, 2022)
Dry pomegranate peel was extracted with acetone and the extract was added to a Phillips type polyethylene. The concentration of the extract was changed from 0 to 1000 ppm in six steps and stabilization efficiency was checked by the multiple extrusion of the polymer followed by the characterization of chemical structure, processing, and residual stability. The results confirmed the excellent processing stabilization efficiency of the extract, but also the poor long-term stability of PE containing it in accordance with previously published results. The extract is amorphous and its solubility is relatively large in the polymer; thus, these factors cannot be the reason for the poor stabilization efficiency in an oxygen-rich environment. Chemical factors like the self-interaction of the polyphenol molecules, the stability of the radicals forming after hydrogen abstraction, and the lack of hydrogens with the necessary reactivity must be considered during the evaluation of the efficiency of the extract. These factors as well as the insufficient number of active hydrogens hinder the reaction of the additive molecules with oxygen-centered radicals, thus leading to inferior long-term stability. The extract can be used for the processing stabilization of polymers, but for applications requiring long-term stability, it must be combined with other natural antioxidants like flavonoids or Vitamin E.